Pre-operative Color Doppler Ultrasonography Predicts Endovenous Heat Induced Thrombosis after Endovenous Radiofrequency Ablation. (July 2018) - Lomazzi, Chiara; Grassi, Viviana; Segreti, Sara; Cova, Marta; Bissacco, Daniele; Bush, Ruth L.; Trimarchi, Santi
Abstract : Objectives: The aim was to identify pre-operative color Doppler ultrasound (CDUS) variables predictive of post-operative endovenous heat induced thrombosis (EHIT) after radiofrequency ablation (RFA) of the saphenous veins. Design: This was a single centre, observational study with retrospective analysis of consecutive patients treated from December 2010 to February 2017. Materials and methods: Pre-operatively, the diameter of the sapheno-femoral junction (dSFJ), distance between superficial epigastric vein and SFJ (dSEV–SFJ), maximum great saphenous vein (GSV) diameter (mdGSV), diameter of the saphenous–popliteal junction (dSPJ), and maximun small saphenous vein (SSV) diameter (mdSSV) were measured. All patients received low molecular weight heparin (LWMH) at a prophylactic dose for a week. Post-operatively, CDUS was performed after 72 h, 1 week, and 3 months. Results: Venous interventions on 512 patients were performed: 449 (87.7%) underwent RFA of the GSV (Group 1), and 63 (12.3%) of the SSV (Group 2). At Day 3 post-operatively, CDUS documented 100% complete closure of the treated saphenous vein segment. Overall, 40 (7.8%) cases of post-operative EHIT were identified: 29 in Group 1, and 11 in Group 2 (6.4% vs. 17.5%, p = .005). Deep venous thrombosis or pulmonary embolism did not occur in either group. At the 1 month follow up, all cases of EHIT regressed. In Group 1, on multivariate analysis, dSEV–SFJ (OR, 1.13, p = .036; 95% CI 1.01–1.27) was the only statistically significant predictor for EHIT. A dSEV–SFJ distance of 4.5 mm yielded an 84% of sensitivity for EHIT prediction with a 72.4% positive predictive value. In Group 2, univariate analysis did not identify independent risk factors for EHIT occurrence. Conclusions: EHIT was higher than previously reported. The dSEV–SFJ was the most significant predictor for EHIT in the GSV group.